Metatranscriptomic assessment of diarrhoeic faeces reveals diverse RNA viruses in rotavirus group A infected piglets and calves from India - Sawant, Pradeep; Kulkarni, Abhijeet; Mane, Rajkumar; Patil, Renu; Lavania, Mallika (Frontiers in Cellular and Infection Microbiology, 2023)
RNA viruses are a major group contributing to emerging infectious diseases and neonatal diarrhoea, causing morbidity and mortality in humans and animals. Hence, the present study investigated the metatranscriptomic-derived faecal RNA virome in rotavirus group A (RVA)-infected diarrheic piglets and calves from India. The viral genomes retrieved belonged to Astroviridae in both species, while Reoviridae and Picornaviridae were found only in piglets. The nearly complete genomes of porcine RVA (2), astrovirus (AstV) (6), enterovirus G (EVG) (2), porcine sapelovirus (PSV) (2), Aichivirus C (1), and porcine teschovirus (PTV) (1) were identified and characterised. In the piglet, AstVs of PAstV2 (MAstV-26) and PAstV4 (MAstV-31) lineages were predominant, followed by porcine RVA, EVG, PSV, Aichivirus C, teschovirus (PTV-17) in decreasing order of sequence reads. In contrast, AstV accounted for the majority of reads in bovines and belonged to MAstV-28 and a proposed MAstV-35. Both RVA G4P[6] strains exhibited prototype Gottfried strains like a genotypic constellation of G4-P[6]-I1-R1-C1-M1-A8-N1-T1-E1-H1. Ten out of eleven genes were of porcine origin, while the VP7 gene clustered with G4-lineage-1, consisting of human strains, suggesting a natural porcine-human reassortant. In the recombination analysis, multiple recombination events were detected in the PAstV4 and PAstV2 genomes, pointing out that these viruses were potential recombinants. Finally, the study finds diverse RNA virome in Indian piglets and calves for the first time, which may have contributed to diarrhoea. In the future, the investigation of RNA virome in animals will help in revealing pathogen diversity in multifactorial diseases, disease outbreaks, monitoring circulating viruses, viral discovery, and evaluation of their zoonotic potential.